ANALISIS FREKUENSI PADA UJI TAK MERUSAK ULTRASONIK - Amoranto Trisnobudi (Mesin, 2005)
In ultrasonic nondestructive testing an ultrasonic wave is usually radiated through a material by a transducer. If there is a flaw inside the material, reflected or diffracted waves caused by the interaction between the ultrasonic wave and the flaw, are received by the same or another transducer. The received signals must be processed in order to obtain information about the flaw characteristics. For the flaw which perpendicular to the beam wave, the flaw size can be determined by amplitude analysis, for example by using DGS (Distance Gain Scale) diagram. The oblique flaw can be characterized by time analysis such as Time of Flight Diffraction (TOFD) method. But if the flaw is small or there is a large enough noise, frequency analysis must be used. This paper deals with the two methods using frequency analysis, i.e. ultrasonic spectroscopy and split spectrum processing, to overcome the above problems.